2013
DOI: 10.1002/cmdc.201300273
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elaboration of a Natural Product: Identification of 3,3′‐Diindolylmethane Aminophosphonate and Urea Derivatives as Potent Anticancer Agents

Abstract: An approach involving rational structural elaboration of the biologically active natural product diindolylmethane (DIM) with the incorporation of aminophosphonate and urea moieties toward the discovery of potent anticancer agents was considered. A four-step approach for the synthesis of DIM aminophosphonate and urea derivatives was established. These novel compounds showed potent anticancer activities in two representative kidney and colon cancer cell lines, low toxicity to normal cells, higher potency than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…However, the reduction of the nitro group to the corresponding free amine was found to be difficult, and in situ acylation derivatization was needed. Yet, although all of these synthetic strategies are useful, they have some limitations in terms of the requirement for stoichiometric amounts of promoters or activators (e.g., Lewis or Brønsted acids), and/or the deprotection step is low yielding and limited by poor functional‐group tolerance 12. Consequently, the development of new, catalytic and efficient methods to broaden the substrate scope and enhance the selective construction of such molecules is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduction of the nitro group to the corresponding free amine was found to be difficult, and in situ acylation derivatization was needed. Yet, although all of these synthetic strategies are useful, they have some limitations in terms of the requirement for stoichiometric amounts of promoters or activators (e.g., Lewis or Brønsted acids), and/or the deprotection step is low yielding and limited by poor functional‐group tolerance 12. Consequently, the development of new, catalytic and efficient methods to broaden the substrate scope and enhance the selective construction of such molecules is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many times, structurally derived compounds have been found to interact with a new molecular target, rather than an original one. Podophyllotoxin is tubulin polymerization inhibitor, 3 whereas its synthetic derivative etoposide is a topoisomerase II-inhibitor (TopoII).…”
mentioning
confidence: 99%
“…DIM is considered to be a promising natural cancer preventive agent. Although DIM has been proven to impart antitumor effects on numerous cancers both in vitro and in vivo (4)(5)(6)(7)(8)(9)11,13,(15)(16)(17)(18)(19), its antimetastatic effects in colorectal cancer and the underlying mechanism have not been fully elucidated. In the present study, we demonstrated that DIM inhibits the migration and invasion of colorectal cancer cells by inactivation of FOXM1 and subsequent downregulation of uPA and MMP9.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer preventive role of 3,3'-diindolylmethane (DIM) in several types of cancer cells has been highlighted, and several studies have proposed DIM as a potent natural dietary compound that reduces colorectal cancer risk and performs several antitumor activities (4)(5)(6)(7)(8)(9)(10)(11). These functions include inhibition of colorectal cancer cell proliferation by suppression of YAP through an Akt-dependent process, alteration of cell cycle progression, and activation of caspase-8 to induce apoptosis (6,10,11).…”
Section: Introductionmentioning
confidence: 99%